2019
DOI: 10.1161/hypertensionaha.119.12853
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Estimation of Aortic Stiffness Through Different Approaches

Abstract: Aortic pulse wave velocity is a worldwide accepted index to evaluate aortic stiffness and can be assessed noninvasively by several methods. This study sought to determine if commonly used noninvasive devices can all accurately estimate aortic pulse wave velocity. Pulse wave velocity was estimated in 102 patients (aged 65±13 years) undergoing diagnostic coronary angiography with 7 noninvasive devices and compared with invasive aortic pulse wave velocity. Devices evaluating carotid-femoral pulse wave velocity (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 27 publications
1
74
0
2
Order By: Relevance
“…Our results, indicating a strong dependence of o-PWV estimates on age and SBP (r 2 0.88), confirm data of previous studies, in which a comparable correlation was found [21,22,33].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results, indicating a strong dependence of o-PWV estimates on age and SBP (r 2 0.88), confirm data of previous studies, in which a comparable correlation was found [21,22,33].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we compared two non-invasive devices for the assessment of PWV based on two different techniques, a tonometric and an oscillometric one. As discussed above, several studies have previously confirmed a good agreement between the two methods and with the invasive intra-aortic measurements (gold standard) [33,[35][36][37][38]. It is however important to note that the two techniques use two different methodologies for the assessment of PWV, which can in part explain the difference in the PWV estimates provided [39,40].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent evidence emphasizes the limitations of the algorithmic approach used by these ABPM devices in measuring central BP and PWV, because in some devices the algorithmic estimate of PWV is only based on squared age values and arm cuff systolic BP and is not really measured, thus being unable to pick‐up alterations in aortic wall properties in specific types of patients, for example, in Marfan's syndrome patients …”
Section: Devices and Softwarementioning
confidence: 99%
“…There are several different tools to non-invasively assess PWV, including tonometric and oscillometric methods as well as CMR-based techniques [49,50]. Many studies focus on comparing different approaches to PWV assessment and try to determine the simplest and most reliable methods that could be helpful in everyday practice [49,51,52]. Recent research, dedicated to comparing different CMR-based techniques of aortic stiffness evaluation in hemodialysis patients, demonstrated excellent inter-and intra-observer variability of ascending and descending AD as well as aortic PWV measurements.…”
Section: Aortic Stiffnessmentioning
confidence: 99%